Kesadaran Pajak, Transparansi dan Kualitas Layanan: Dampak Kepatuhan Dimoderasi oleh Penggunaan Surat Keterangan Pemotongan Pajak Secara Elektronik - Joni Joni; Estralita Trisnawati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study investigates the influence of tax awareness, transparency and service quality on taxpayer compliance, specifically examining the moderating role of e-Bupot. The research was conducted at KPP Pratama Batam Selatan, utilizing a quantitative approach with a sample of 100 taxpayers. Primary data were collected via questionnaires and analyzed using the PLS-SEM method with SmartPLS 3.0. The empirical confirm that Tax Awareness and Transparency show a positive significant influence on Taxpayer Compliance across both regression models. Service Quality only achieved a significant positive effect in the more comprehensive moderated model, indicating the importance of administrative support. The E-Bupot digital platform proved to be a selective yet critical moderator. It significantly strengthened the positive effects of both Tax Transparency and Service Quality, acting as a powerful catalyst for systemic and procedural efficiency. Conversely, E-Bupot's interaction with Tax Awareness was not significant. This outcome implies that high internal awareness is insufficient for maximizing digital compliance efforts without corresponding digital literacy and technological readiness among taxpayers.